Samaṇ Śreṇi: Migration, Social Movement and Religious Change - Anton Zykov (Orientalia Suecana, 2020)
The article tries to explain the recent emergence of the new religious rank within the Jain Śvetāmbar Terāpãth community in India. Traditional Jainism makes a clear distinction between two groups of followers, namely ascetic monks and laymen. Under the sect’s late leader Ācārya Tulsi (1914–1997), prolific author and founder of the Vishva Bharati Institute in Ladnun (Rajasthan), an intermediary rank between the ‎monks and the laity was introduced. This paper argues that the main motivation to introduce the new rank follows socio-economic considerations relating to the large and economically prospering Jain diaspora that has been growing outside of ‎India in recent decades. The paper discusses the foundation and ‎development of the Samaṇ Śreṇi, as the new rank became known, through original materials published by ‎the community as well as fieldwork findings and interviews made in the Śvetāṃbar religious centre of Ladnun (Rajasthan).